Toward sustainable and smart cities in Africa: a review and challenges - Dos Santos, Maria José Palma Lampreia (2020)
This paper aims to present the main challenges to overcome in order to have sustainable and smart cities in Africa in the future, by analyzing social, economic, environmental, and political problems in African regions/cities. This study is particularly relevant as the problems of sustainable development in this region and the task of finding the solutions to minimize them became world problems, since they will affect the world sustainable development. It is also important to note that although there are many studies in the scientific field of smart cities, few of them had analyzed the topic of smart cities and sustainability and none of them so far analyzed the complex situation in African cities nor brought to the scientific debate and forecast new insights about these topics. The holistic approach was used to analyze sustainable and smart cities in Africa is believed to be the first of its kind and hence has not been, to the best of our knowledge, produced elsewhere. This paper gives insights to stakeholders and public decision-makers about the way forward in the promotion and development of cities in Africa in a sustainable way, in order to foster research in these innovative areas. It also broadens new research opportunities to explore and bring more knowledge in smart sustainable cities in general and in Africa in particular.